Rehabilitation after Cardiac Arrest: Integration of Neurologic and Cardiac Rehabilitation - Boyce, Liesbeth W.; Goossens, Paulien H. (Seminars in Neurology, 2017)
Cognitive impairments are common after resuscitation. Severe cognitive impairments are easily recognized. Mild cognitive impairments are much more difficult to spot. Given the influence of cognitive problems in daily functioning, it is important to identify cognitive impairments at an early stage. Also, emotional problems, mainly depression and fear, are common in this group of patients. To optimize the care for patients after an out-of-hospital cardiac arrest, rehabilitation should focus on the physical approach through cardiac rehabilitation and on brain injury and associated cognitive impairments. The goal of rehabilitation after a cardiac arrest is to provide excellent patient-centered cardiac and cognitive rehabilitation to all patients and their spouses to achieve optimal participation in society, with minimal burden for spouses and society. To achieve this, cardiac and cognitive rehabilitation need to be coordinated in an integrated care path.
Keywords: out-of-hospital cardiac arrest; cognitive impairments; cognitive rehabilitation; cardiac rehabilitation; integrated health care systems